PENERAPAN AKUNTANSI OLEH BISNIS SKALA KECIL PADA SEKTOR PARIWISATA DI UBUD - Ni Made Sri Rukmiyati (JURNAL KEPARIWISATAAN, 2020)
The financial report is one of the absolute components that must be owned by small and medium enterprises if they want to propose capital to creditors, in this case, the banking sector. In addition to financing, financial reports can certainly provide useful financial information for effective planning and evaluation of company performance. The purpose of this research is to find out how the application of accounting by small-scale businesses in the tourism sector in Ubud and the obstacles faced in applying accounting. The data analysis technique used in this research is descriptive qualitative where this analysis technique is used to describe the research data. The data collection method uses observation, interview, and documentation study techniques. Most of the respondents, namely 77% have separated personal and business finances, this reflects professionalism in the management of company finances. Respondents in this study who had made financial reports were 77% even though most respondents only made income statements. Overall, most of the respondents have implemented simple accounting practices in their businesses, but they still lack awareness in increasing their knowledge in accounting through accounting training / seminars.